Domestic Wastewater Treatment Using Vermiculture - ., Jothilakshmi; ., Sivaranjani; ., Subasri; ., Thilagavathy; ., Vishali (International Journal of Engineering and Technology, 2018)
The organic matter helps in various bioprocesses. Management of organic waste is challengingÂ Â because of the improper disposal causing hazards to the environment. The sludge from the sewage treatment plant is dumped as landfill and used as fertilizer in agricultural operation. This action may solve the disposal of quantity of sewage sludge but the environment is highly affected by the pathogens. Nowadays vermicomposting is used for the removal of pathogens in organic matter. It includes accelerated treatment of nutrients in which waste end products are put to useful end products. When this method of vermicomposting Â is used in domestic wastewater management considerable reduction in pathogens was found in the organic waste so that the end product can be safely applied safely to land. This work Â gives a view of the management of domestic waste water utilizing vermiculture. The process can be used for household waste treatment and rural or urban waste management in a small scale.Â Â Â